Modelling and simulation of a series excited synchronous motor - Özdemir, Mehmet; Önbilgin, Güven (My University, 2001)
This study attempts to build up a mathematical model, for a type af series excited synchronous motor. This model, when used for simulation, is expected to yield the dynamic behaviour of the system for typical cases such as asynchronous start-up, synchronising and synchronous operation. The model consists of a set of differential equations involving semiconductor switching with constant topology and variable parameters and utilises phase variables. But an inter-conversion between phase variables and space phasors is required to take into account the magnetic saturation. The model is then used for a sample system, to enable a comparison between experimental and computed results. This comparison is used to assess the accuracy, validity and usefulness of the model. Furthermore, steady-state behaviour of the scheme is explained by means of a simple analysis and illustrated by test results.
Modeliranje i simulacija serijski pokrenutog sinkronog motora
Keywords: Magnetic saturation; Mathematical model; Synchronous motor